Sex Differences in Quality of Life in Patients With Atrial Fibrillation: A Systematic Review - Strømnes, Linn Arvidsson (J Am Heart Assoc, 2019)
BACKGROUND: The goal of this literature review was to assess sex differences in the quality of life (QoL) in patients with atrial fibrillation (AF) and, if possible, to determine if these are due to AF. METHODS AND RESULTS: The electronic database PubMed was searched on January 23, 2018, using the search terms “QoL”, gender differences, “AF” female, and gender to find potential articles that assessed sex differences in QoL in AF patients. In all, 851 articles were identified, from which 25 original studies were eligible for this systematic review. Female AF patients were found to have poorer QoL and more symptoms than male AF patients. They scored lower, predominantly on the physical component score of the Medical Outcomes Study Short‐Form 36 Health Survey. CONCLUSIONS: The available literature consistently describes poorer QoL in female AF patients but does not clearly address whether this is a reflection of sex differences seen in the general population or is related to AF per se. It is also questionable whether the relatively poorer QoL in women is large enough to be of clinical importance.